Axisymmetric finite cylinder with rigid ends and a circumferential edge crack - Durucan, Ayşe Ruşen (Kahramanmaras Sutcu Imam University, 2018)
An axisymmetric linearly elastic and isotropic finite cylinder with rigid ends and a circumferential edge crack subjected to axial tension is considered. Finite cylinder problem is obtained from an infinite cylinder containing an internal ring-shaped crack and two penny-shaped rigid inclusions. Navier equations are solved by using Fourier and Hankel transforms. Formulation is reduced to three singular integral equations which are converted to a system of linear algebraic equations with the aid of Gauss-Lobatto and Gauss-Jacobi integration formulas. Stress intensity factors at the edges of crack and around the corner of the cylinder are calculated.

Bu çalışmada doğrusal elastik ve izotropik malzemeden imal edilmiş, çevresel bir kenar çatlağı içeren rijit uçlu sonlu uzunlukta eksenel simetrik bir silindir incelenmiştir. Sonlu silindir problemine ulaşmak için, halka şeklinde iç çatlak ve iki dairesel şekilli enklüzyon içeren sonsuz bir silindirden yola çıkılmıştır. Navier denklemleri Fourier ve Hankel dönüşümleri kullanılarak çözülmüştür. Formülasyon tekil integral denklemlerine indirgenmiş ve Gauss-Lobatto ve Gauss-Jakobi integrasyon formülleri ile doğrusal cebrik denklem takımlarına dönüştürülmüştür. Çatlağın kenarlarındaki ve silindirin çevresi etrafındaki gerilme yığılma faktörleri hesaplanmıştır.
Çevresel kenar çatlağı içeren rijit uçlu eksenel simetrik sonlu silindir
Keywords: Civil Engineering; İnşaat Mühendisliği